Factors Associated with The Motivation of Palm Sugar Producers in Malapari Village Muara Bulian Batanghari Regency - Rosyani, Rosyani; Sativa, Fendria; Adinda Nugraha, Naila (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2026)
This study aims to describe the factors associated with the motivation of palm sugar producers in Malapari Village, Muara Bulian Sub-district, Batanghari Regency; to describe the motivation of palm sugar producers in Malapari Village, Muara Bulian Sub-district, Batanghari Regency; and to analyze the factors associated with the motivation of palm sugar producers in Malapari Village, Muara Bulian Sub-district, Batanghari Regency. This research was conducted in Malapari Village, Muara Bulian Sub-district, Batanghari Regency. This area was selected based on the consideration that Malapari Village is the center for palm sugar production in Batanghari. The collected data were analyzed using non-parametric statistics through the Chi-Square test. The results obtained from the study are: 1) The factors associated with the producer’s motivation tend to be high, with the following percentages: education factor 58%, experience factor 65%, raw material availability factor 58.3%, tradition factor 53%, sales factor 78%, and government policy factor 63%. 2) The motivation of palm sugar producer in Malapari Village tends to be high, with the following percentages for its aspects: Existence 80%, Relatedness 76.6%, and Growth 90%. The overall aspect of motivation is 75%. 3) Based on the Chi-Square analysis results, there is a significant relationship between the factors and the motivation of palm sugar producer in Malapari Village, Muara Bulian Sub-district, Batanghari Regency at the 95% significance level.